2023
DOI: 10.1021/acsami.2c20265
|View full text |Cite
|
Sign up to set email alerts
|

Force-Mediated Endocytosis of Iron Oxide Nanoparticles for Magnetic Targeting of Stem Cells

Abstract: Stem cell therapy represents one of the most promising approaches for tissue repair and regeneration. However, the full potential of stem cell therapy remains to be realized. One major challenge is the insufficient homing and retention of stem cells at the desired sites after in vivo delivery. Here, we provide a proof-of-principle demonstration of magnetic targeting and retention of human muscle-derived stem cells (hMDSCs) in vitro through magnetic force-mediated internalization of magnetic iron oxide nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Biocompatibility studies with human umbilical vein endothelial cells (HUVECs) showed that endocytosis is the main mechanism of the intracellular transport of dextran- and citric acid-coated SPIONs. Additionally, SPIONs were found to inhibit the migration and induce apoptosis of HUVECs [ 60 ]. An in vivo animal study revealed that the pharmacokinetics and biodistribution of MNPs were dependent on the mode of administration, hydrodynamic diameter, and surface charge.…”
Section: Use Of Mnps With Locally Induced Htmentioning
confidence: 99%
“…Biocompatibility studies with human umbilical vein endothelial cells (HUVECs) showed that endocytosis is the main mechanism of the intracellular transport of dextran- and citric acid-coated SPIONs. Additionally, SPIONs were found to inhibit the migration and induce apoptosis of HUVECs [ 60 ]. An in vivo animal study revealed that the pharmacokinetics and biodistribution of MNPs were dependent on the mode of administration, hydrodynamic diameter, and surface charge.…”
Section: Use Of Mnps With Locally Induced Htmentioning
confidence: 99%
“…In addition, SPION can be used for drug delivery and magnetic thermotherapy. In drug delivery, drugs can be encapsulated in NPs and delivered precisely to the lesion site by magnetic field induction, thereby improving drug efficacy and reducing side effects 147–149 . As for magnetic hyperthermia, the heat generated by NPs in an alternating magnetic field (AMF) can be used to kill tumor cells, thus achieving the goal of treating tumors 150–152 .…”
Section: Overview Of Npsmentioning
confidence: 99%
“…In drug delivery, drugs can be encapsulated in NPs and delivered precisely to the lesion site by magnetic field induction, thereby improving drug efficacy and reducing side effects. 147 , 148 , 149 As for magnetic hyperthermia, the heat generated by NPs in an alternating magnetic field (AMF) can be used to kill tumor cells, thus achieving the goal of treating tumors. 150 , 151 , 152 In conclusion, SPION is a promising nanomaterial with a wide range of applications, and research on its preparation and application is constantly deepening and developing.…”
Section: Overview Of Npsmentioning
confidence: 99%
“…Previous studies have established that nanoparticles encapsulated in phospholipid-PEG coating are internalized by cells through endocytic pathways, accumulating in endosomes and lysosomes with pH levels ranging from 4 to 5. 39 Taken together, when only intracellular WNPs are present, ascorbic acid can generate H 2 O 2 in the medium, which then permeates cells and encounters WNPs accumulated in the acidic cell organelles. Under optimal pH conditions, WNPs efficiently convert H 2 O 2 into toxic hydroxyl free radicals.…”
Section: Interaction Between Wnps and Ascorbic Acid In Cell Culturementioning
confidence: 99%